Circ_0092367 Inhibits EMT and Gemcitabine Resistance in Pancreatic Cancer via Regulating the miR-1206/ESRP1 Axis - Shuo Yu (MDPI AG, 2021)
Gemcitabine is the first-line treatment for patients with pancreatic cancer (PC), yet most patients develop resistance to gemcitabine. Recent studies showed that circular RNAs (circRNAs) have important regulatory roles in PC progression and chemoresistance. In this study, the ability of circRNA circ_0092367 to enhance gemcitabine efficacy was tested and the underlying molecular mechanism of circ_0092367 was investigated. The expression levels of circ_0092367, miR-1206, and ESRP1 were measured using qRT-PCR experiments. The effects of circ_0092367, miR-1206, and ESRP1 on PC cell lines exposed to gemcitabine were examined by CCK-8 assays. We performed luciferase assays to determine the relationship between circ_0092367 and miR-1206 and between miR-1206 and ESRP1. We demonstrated that circ_0092367 was significantly downregulated in PC tissues and cell lines, and a high expression of circ_0092367 was associated with improved survival in patients with PC. Gain- and loss-of-function assays revealed that circ_0092367 inhibited epithelial–mesenchymal transition (EMT) phenotypes and sensitized PC cells to gemcitabine treatment in vitro and in vivo. Cytoplasmic circ_0092367 could directly repress the levels of miR-1206 and thus upregulate the expression of ESRP1, thereby inhibiting EMT and enhancing the sensitivity of PC cells to gemcitabine treatment. Our findings show that circ_0092367 plays a crucial role in sensitizing PC cells to gemcitabine by modulating the miR-1206/ESRP1 axis, highlighting its potential as a valuable therapeutic target in PC patients.